1993
DOI: 10.1093/cvr/27.11.2065
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity of Gi protein mediated muscarinic receptor adenylyl cyclase in chronic ischaemic heart failure in the rat

Abstract: The experimental chronic failing heart due to myocardial ischaemia showed a depressed myocardial adenylyl cyclase signalling system. This may be due to the hypersensitivity of the Gi protein mediated muscarinic receptor-adenylyl cyclase system as shown by the increased inhibition of Gpp(NH)p mediated adenylyl cyclase, more potent inhibition of stimulated adenylyl cyclase by carbachol, and the superhigh affinity of the muscarinic receptors for carbachol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…Second, whereas rapid atrial pacing has been shown to cause dramatic effects on sinus node function, no differences were found in sinus node function with rapid ventricular pacing (11). Finally, and perhaps most convincing that the effects seen here are not related to the pacing model per se, are the findings by other investigators that changes in muscarinic receptor function involving G proteins are consistent across pacing-induced HF in dogs (42) and dilated idiopathic cardiomyopathy in humans (15,16,23). Therefore, whereas we cannot exclude the effects of tachycardia alone, these results are more consistent with an effect due to the HF state itself.…”
Section: Limitations Of Studysupporting
confidence: 60%
“…Second, whereas rapid atrial pacing has been shown to cause dramatic effects on sinus node function, no differences were found in sinus node function with rapid ventricular pacing (11). Finally, and perhaps most convincing that the effects seen here are not related to the pacing model per se, are the findings by other investigators that changes in muscarinic receptor function involving G proteins are consistent across pacing-induced HF in dogs (42) and dilated idiopathic cardiomyopathy in humans (15,16,23). Therefore, whereas we cannot exclude the effects of tachycardia alone, these results are more consistent with an effect due to the HF state itself.…”
Section: Limitations Of Studysupporting
confidence: 60%
“…Since muscarinic receptor-mediated inhibition of adenylyl cyclase to some extent balances the effect of P-adrenergic-mediated stimulation of the adenylyl cyclase system in myocardium, changes in any of the various components in the inhibitory G-protein (Gi)-mediated muscarinic receptor signaling system could therefore be expected to also occur in cardiomyopathy or diabetes induced cardiac dysfunction. We and others have previously demonstrated an increase in Gi function not only in failing human heart due to dilated cardiomyopathy but also in failing rat heart due to chronic ischemia (Bohm et al 1990;Fu et al 1992bFu et al & 1993. The first ojective of the present study was, therefore, to examine the biochemical changes in the Gi-mediated muscarinic receptor-adenylyl cyclase system in diabetes induced cardiac dysfunction.…”
mentioning
confidence: 78%
“…The reaction was linear within 10 min. and with respect to a protein content of 20-50 pgi25 p1 (Fu et al 1992b(Fu et al & 1993.…”
Section: Peptide Synthesis and Antibody Purijicationmentioning
confidence: 99%
“…1113 However, it is unclear whether GRK-mediated phosphorylation of β 2 AR is involved in the regulation of β 2 AR-coupled G i signaling in heart. Because both GRK2 and G i proteins are significantly elevated in HF caused by a multitude of etiologies, 1419 we hypothesize that the well-documented detrimental effects of GRK2 in the failing heart may causatively link to enhanced β 2 AR-coupled G i signaling.…”
Section: Introductionmentioning
confidence: 99%